MARKET MECHANISMS OF SPACIOUS ORGANIZATION OF LAND RESOURCES – A CASE STUDY IN CHERNIVTSI DISTRICT, UKRAINE - Oleksandr BOCHKO; Ivan RIY (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this research is to study the market mechanisms of spatial organization of land resources on the basis of the development and implementation of a system of crop rotation on arable land, and ways of forming plant communities on forage lands.The systematic approach to sustainable development is the leading methodology of territorial organization of land use and environmental protection. The technique of creating a sustainable agro-landscape through the formation of an ecologically adapted organization of agricultural land is proposed. The mechanism of spatial organization of land resources is carried out in accordance with the pro-posed methodologies: the composition of crop rotations and grass mixtures is correlated with the corresponding agro-economic group. The technique was tested on the territory of Chernivtsi district of Vinnytsia region. The article provides an overview of the historical development and state of implementation of concepts and tools for land-use planning and land-use management for land resources and landscapes, and pro-vides recommendations for future action. These issues are especially relevant for agricultural land, as well as for other categories of land subject to anthropogenic loading in the conditions of agrarian production extensification and modern globalization challenges. It is proposed to define the spatial system of organization of land resources as a functional, structural transformation, which implies a certain placement of components of the natural, social and economic environment in space and its spatial indivisibility. In this case, the main role is given to land resources, namely agricultural land. It has been proven that agricultural land use planning and, more broadly, land planning are tools for achieving sustainable and efficient use of resources, taking into account biophysical and socio-economic dimensions. In order to solve this problem, mechanisms of spatial organization of land resources have been developed using the example of Chernivtsi district. The ecologically adapted area of crops’sowing of Chernivtsi district, Vinnitsa region is calculated.